Prevalence, Impact, and Management Practice of Dysmenorrhea among University of Gondar Students, Northwestern Ethiopia: A Cross-Sectional Study - Minaleshewa Biruk Gebeyehu; Abebe Basazn Mekuria; Yonas Getaye Tefera; Dagmawi Abate Andarge; Yabsira Belayneh Debay; Geremew Sokile Bejiga; Begashaw Melaku Gebresillassie (Hindawi Limited, 2017)
Background. Dysmenorrhea is an important health problem of adolescents in school, as well as health practitioners, that badly affects the daily activities and quality of life. The aim of this study was to measure the prevalence of dysmenorrhea and assess its management practice among University of Gondar students. Methods. A cross-sectional study was done from April 06 to May 08, 2016, on female students of University of Gondar. Descriptive and binary logistic regression analyses were used to describe and assess the association between different variables. Results. More than two-thirds (75.3%) of the respondents were nonmedical students and the prevalence of dysmenorrhea was 77.6%. About half (50.6%) of the participants reported that they have a family history of dysmenorrhea and experienced continuous type of pain (53%) which lasts 1-2 days (47.8%). Abdominal spasm (70.4%), back pain (69.7%) fatigue, and weakness (63.5%) were the most commonly experienced dysmenorrhea symptoms. More than half (63%) of the respondents had encountered social withdrawal and decrease in academic performance (51.4%). More than two-thirds (63.8%) of the respondents use home remedies as a primary management option. Ibuprofen and diclofenac were the most commonly used medications to manage dysmenorrhea. Conclusions. The present study revealed that high proportion of University of Gondar female students had dysmenorrhea. Findings suggest the need for educating adolescent girls on appropriate and effective management of dysmenorrhea.